2020
DOI: 10.5582/irdr.2020.03092
|View full text |Cite
|
Sign up to set email alerts
|

Two new missense mutations in the protein interaction ASH domain of OCRL1 identified in patients with Lowe syndrome

Abstract: The oculocerebrorenal syndrome of Lowe is a rare X-linked disease characterized by congenital cataracts, proximal renal tubulopathy, muscular hypotonia and mental impairment. This disease is caused by mutations in the OCRL gene encoding membrane bound inositol polyphosphate 5-phosphatase OCRL1. Here, we examined the OCRL gene of two Lowe syndrome patients and report two new missense mutations that affect the ASH domain involved in protein-protein interactions. Genomic DNA was extracted from peripheral blood of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Therefore, numerous studies have shown that OCRL-1 is preoccupied with various cellular activities having endocytic trafficking and skeletal dynamics of actin. These findings explain the different clinical symptoms of the disease (12,13).…”
mentioning
confidence: 61%
See 3 more Smart Citations
“…Therefore, numerous studies have shown that OCRL-1 is preoccupied with various cellular activities having endocytic trafficking and skeletal dynamics of actin. These findings explain the different clinical symptoms of the disease (12,13).…”
mentioning
confidence: 61%
“…The prenatal and postnatal distinctions are made by enzymatic and molecular analyses (2). Molecular studies should approve the clinical diagnosis of the OCRL1 gene; however, unfortunately, it is impossible to diagnose and evaluate all patients before birth (1,5,9,12,18). Before giving birth, it is necessary to check all suspected patients or family history (6,8,9).…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations